Possible Impacts of Distrainer's Agents Territoriality - SMRČKA, Luboš; ČÁMSKÁ, Dagmar; PLAČEK, Jan (Journal of Advanced Research in Law and Economics, 2016)
This paper deals with a possible legal framework change influencing distrainer's agents or bailiffs in the Czech Republic. The main aim of this paper is to estimate possible impacts of this regulatory change. There should occur serious shift how individual cases are redistributed among enforcement agents due to principle of territoriality. There is a lack of data about enforcement agents functioning and therefore this paper uses also standard microeconomic theory for forecasting than only data processing. The estimates based on data are focused on the number of solved cases but also on number of employees of distrainer's offices. The forecasts based on the classical microeconomic theory mainly and partly on behavioral economics deal with the system efficiency. Possible consequences of the legal framework change in the case of territoriality of distrainer's offices or individual agents are presented in the paper.
Keywords: Czech Republic; receivables enforcement; impacts of territoriality; forecasting